Frontopolar Resource Allocation in Human and Nonhuman Primates. Issue 2 (February 2016) - Pollmann, Stefan
Abstract : A recent report suggested that monkey frontopolar cortex (FPC) is vital for the reallocation of cognitive resources among potential goals in complex underspecified situations. These findings nicely complement evidence from human neuroimaging and patient studies, leading to a common conceptual framework of FPC function across species.